Comparison of the Effectiveness of Ajwa Date (Phoenix dactylifera L.) Flesh and Seed Extracts against Aggregatibacter actinomycetemcomitans Bacteria with 70% and 100% Concentrates - Tari Dwi Pratiwi; Minantari Sihotang; Icha Amanda Hasturi Lubis; Kamilah Almadani; Annisa Rizkia Ginting (Journal Research of Social Science, Economics, and Management, 2026)
Abstrak. Aggregatibacter actinomycetemcomitans is a bacterium that causes aggressive periodontitis. Prevention efforts use antibacterial compounds. The purpose of this study was to compare the antibacterial effectiveness of Ajwa date (Phoenix dactylifera L.) flesh and seed extracts against Aggregatibacter actinomycetemcomitans at concentrations of 70% and 100%. This type of research is an experimental study using a post-test control only design using the disc diffusion technique. The study population was a pure culture of Aggregatibacter actinomycetemcomitans that had been cultivated at the Integrated Laboratory of Prima Indonesia University. A total of 36 samples were divided into 6 groups. Antibacterial testing used the disc diffusion method, which measures the diameter of the inhibition zone in millimeters. Data analysis was carried out using Kruskal-Wallis and Mann-Whitney. The results showed that the average diameter of the inhibition zone of Ajwa date (Phoenix dactlifera L.) flesh at 70% and 100% concentrations was 8,82 ± 1,02 mm and 10,51 ± 1,28 mm. The date seed group at 70% and 100% concentrations showed an average inhibition zone diameter of 15,61 ± 0,72 mm and 16,84 ± 0,57 mm, and chlorhexidine was 19.65±0.380 mm. DMSO as a negative control showed no inhibition against Aggregatibacter actinomycetemcomitans bacteria. The results of the Kruskal-Wallis test can be stated that there is a significant difference in the diameter of the inhibition zone of all groups in Ajwa date flesh and seeds (p=0.000; p<0.05).